2021
DOI: 10.3390/biomedicines9050490
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase in Brain: The New Kid on the Block and Its Role in Neurodegenerative Diseases

Abstract: Telomerase is an enzyme that in its canonical function extends and maintains telomeres, the ends of chromosomes. This reverse transcriptase function is mainly important for dividing cells that shorten their telomeres continuously. However, there are a number of telomere-independent functions known for the telomerase protein TERT (Telomerase Reverse Transcriptase). This includes the shuttling of the TERT protein from the nucleus to mitochondria where it decreases oxidative stress, apoptosis sensitivity and DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 83 publications
(162 reference statements)
0
20
0
Order By: Relevance
“…However, recently, there is evidence on the protective role of TERT in neurons. TERT may activate autophagy for toxic neuronal proteins and ameliorate the effects of amyloid-β, pathological tau, and α-synuclein involved in neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease [41][42][43][44]. TERT is expressed in several regions of the brain, such as the olfactory bulb, cortex [45], hippocampus [46], and subventricular zone and in Purkinje neurons of the cerebellum [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, there is evidence on the protective role of TERT in neurons. TERT may activate autophagy for toxic neuronal proteins and ameliorate the effects of amyloid-β, pathological tau, and α-synuclein involved in neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease [41][42][43][44]. TERT is expressed in several regions of the brain, such as the olfactory bulb, cortex [45], hippocampus [46], and subventricular zone and in Purkinje neurons of the cerebellum [47].…”
Section: Discussionmentioning
confidence: 99%
“…Brain ageing is a key risk factor and mechanism responsible for a number of neurodegenerative diseases ( 32 , 33 ), and it has been demonstrated that telomerase activity and TERT abundance may play a protective role in neurons and brain cell functions ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TERT levels regulate telomerase activity, and it has been described that telomerase activity decreases during embryo-genesis. By contrast, the TERT levels are maintained, at least in humans, possibly to protect neurons from oxidative stress and neurodegeneration ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomerase is present in almost all eukaryotic organisms and was studied firstly in protozoans by Nobel Laureate Elizabeth Blackburn, its importance for human health during development, ageing and cancer soon became obvious [ 98 ].…”
Section: Curcumin and Telomerases In Brainmentioning
confidence: 99%